2006
DOI: 10.1038/sj.embor.7400597
|View full text |Cite
|
Sign up to set email alerts
|

Remodelling epithelial tubes through cell rearrangements: from cells to molecules

Abstract: Epithelial cell movements, such as those that occur during cell intercalation, largely contribute to the formation of epithelial structures during the morphogenesis of multicellular organisms. As the architecture of epithelial tissues relies on strong adhesion between cells at adherens junctions (AJs), the intercalation or rearrangements of epithelial cells might be controlled by modulating the adhesion dynamics of the AJs by internal or external forces. In this review, we describe recent progress in understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…The elongation of the dorsal branch does not occur in the absence of Dpp signaling (Chen et al, 1998), because, by itself, Bnl/FGF only induces filopodial extensions (Ribeiro et al, 2002). Dpp signaling is required to suppress Spalt (Sal) in the DBs, enabling the formation of a unicellular tube through cell intercalation (Ribeiro et al, 2004;Neumann and Affolter, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The elongation of the dorsal branch does not occur in the absence of Dpp signaling (Chen et al, 1998), because, by itself, Bnl/FGF only induces filopodial extensions (Ribeiro et al, 2002). Dpp signaling is required to suppress Spalt (Sal) in the DBs, enabling the formation of a unicellular tube through cell intercalation (Ribeiro et al, 2004;Neumann and Affolter, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…size, length or diameter) were described (Beitel and Krasnow, 2000). The identification and cloning of the genes affected in these and other mutants has shed light on how the specialized apical secretion of ECM material contributes to tube expansion and tube length control.Although the observed size differences between distinct tracheal branches is probably controlled by those genes that regulate branch identity (for example, by the presence or absence of Sal in the cells of the dorsal trunk and the dorsal branches, respectively) (Ribeiro et al, 2004;Neumann and Affolter, 2006; Casanova, 2007), the diameter of certain tubes expands rapidly in a relatively short time frame. The uniform expansion of tube diameter requires the formation of a transient luminal chitin-based matrix (Araujo et al, 2005;Moussian et al, 2006;Tonning et al, 2005;Devine et al, 2005) (reviewed by Swanson and Beitel, 2006) (see Fig.…”
mentioning
confidence: 99%
“…The tracheae are the respiratory organ of Drosophila and genes have been identified that are required for each step of tracheole branching morphogenesis (Samakovlis et al 1996;Petit et al 2002;Neumann and Affolter 2006). These studies identify several signaling pathways conserved in humans, including the GF, TGF-b, Wnt, and Hh pathways.…”
mentioning
confidence: 99%
“…Within the moving cell there are directional changes in actin/myosin polymerization and endocytic shuttling of membrane components to the leading edge. Cell intercalation additionally requires changes in the number and location of ''adherens junctions,'' which are specialized connections between epithelial cells involving catenins, cadherins, and the actin cytoskeleton (Neumann and Affolter 2006). GTPases such as Rho and nucleoside kinases including nm23 (awd) act downstream of Wnt and other pathways to directly regulate cytoskeleton organization and membrane dynamics in the moving cell (Palacios et al 2002;Dammai et al 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation